ASSESSMENT OF ROCURONIUM REVERSAL WITH SUGAMMADEX FOR EARLY TRACHEAL EXTUBATION IN PATIENTS UNDERGOING BRAIN TUMOR RESECTION (Vietnam Journal of Community Medicine, 2026)
Objectives To evaluate the effectiveness of neuromuscular recovery and the adverse effects of sugammadex in reversing rocuronium-induced neuromuscular blockade in patients undergoing brain tumor resection.Methods: A prospective descriptive study was conducted on 30 patients undergoing brain tumor resection at 108 Military Central Hospital from October to December 2025. General anesthesia was induced and neuromuscular blockade was achieved with rocuronium. Neuromuscular function was monitored using a TOF-Watch. At the end of surgery, sugammadex at a dose of 2 mg/kg was administered when the second twitch (T2) appeared in the train-of-four (TOF) stimulation. TOF ratios, hemodynamic parameters (heart rate, blood pressure), respiratory parameters (SpO₂, respiratory rate), time to tracheal extubation, and adverse events were recorded.Results: The mean total dose of rocuronium was 222.54 ± 8.58 mg. The recovery times from T2 to TOF ratios of ≥0.5, ≥0.7, and ≥0.9 were 1.35 ± 0.36 minutes, 1.93 ± 0.42 minutes, and 2.46 ± 0.62 minutes, respectively. The mean time to tracheal extubation was 24.30 ± 2.57 minutes. All patients were fully awake after surgery. One patient developed bradycardia after sugammadex administration. No cases of residual or recurrent neuromuscular blockade were observed, and no significant respiratory or cardiovascular adverse effects were detected.Conclusion: Sugammadex provides rapid reversal of rocuronium-induced neuromuscular blockade, facilitating early tracheal extubation after brain tumor surgery.
Keywords: Brain tumor resection, sugammadex, reversal neuromuscular blockade.